Market Stakeholder Analysis of the Practical Implementation of Carbonation Curing on Steel Slag for Urban Sustainable Governance - Li, Jiajie; Wang, Chenyu; Song, Xiaoqian; Jin, Xin; Zhao, Shaowei; Qi, Zihan; Zeng, Hui; Zhu, Sitao; Jiang, Fuxing; Ni, Wen; Hitch, Michael (MDPI AG, 2022)
Carbonation curing on steel slag is one of the most promising technologies for the iron and steel industry to manage its solid waste and carbon emissions. However, the technology is still in its demonstration stage. This paper investigates the market stakeholders of carbonation curing on steel slag for construction materials for its effective application by taking China as a case study. A holistic analysis of the competition, market size, and stakeholders of carbonation curing on steel slag was carried out through a literature review, a survey, a questionnaire, and interviews. The results showed that carbonation curing on steel slag had the advantages of high quality, high efficiency, low cost, and carbon reduction compared with other technologies. Shandong province was the most suitable province for the large-scale primary application of the technology. Stakeholder involvement to establish information platforms, enhance economic incentives, and promote adequate R&D activities would promote carbonation curing of steel slag into practice. This paper provides a reference for the commercialization of carbonation curing on similar calcium- and magnesium-based solid waste materials.